2020
DOI: 10.32535/jicp.v0i0.904
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Experiential Marketing and E-Service Quality on E-Satisfaction and Repurchase Intention

Abstract: This study aims to investigate the impact of experiential marketing and e-service quality on repurchase intention through e-satisfaction. Information assortment was directed utilizing purposive examination by disseminating to 100 respondents. The aftereffect of this examination demonstrates that : (1) experiential showcasing directly effects on e-satisfaction, (2) e-service quality directly effects on e-service quality, ((3) experiential marketing directly effects on repurchase intention, (4) e-service quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Abdullah (2017) found that consumers with less education and between 18 and 38 of age found that PED is more effective than other groups. These findings were validated by Anggraini et al (2020). In contrast, scholars (Park, 2018;Kim et al, 2020;Singh et al, 2020) suggested that bettereducated individuals strongly believed in the PED and did not show much difference than compared to least-educated consumers, whereas Ahmed et al (2007) and Nair and Shams (2020) failed to show any difference between consumers based on their age, gender, education, occupation and experience.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Abdullah (2017) found that consumers with less education and between 18 and 38 of age found that PED is more effective than other groups. These findings were validated by Anggraini et al (2020). In contrast, scholars (Park, 2018;Kim et al, 2020;Singh et al, 2020) suggested that bettereducated individuals strongly believed in the PED and did not show much difference than compared to least-educated consumers, whereas Ahmed et al (2007) and Nair and Shams (2020) failed to show any difference between consumers based on their age, gender, education, occupation and experience.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Customer satisfaction affects repurchase intention (Weiss et 2005;Soebandhi et al, 2020;Mensah & Mensah, 2018;Lin, 2019;Fang et al, 2011). Experiential marketing affects repurchase intentions (Yuan & Wu, 2008;Subawa, 2020;Suhaily & Soelasih, 2017;Anggraini, Jodi, & Putra, 2020;Friesa Ergo M & Dharmani, 2020). Experiential marketing affects repurchase intentions by mediating customer satisfaction (Rahardja & Anandya, 2010;Steven, Hery Winoto Tj, & Eka Desy Purnama, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Hasil penelitian sejalan dengan penelitian yang dilakukan oleh (Razak, Mokhtar, Rahman, & Abidin, 2021) yang mengatakan bahwa e-service quality memiliki pengaruh langsung maupun tidak langsung terhadap continuous intention to use. Pengaruh tidak langsung didapat melalui efek mediasi dari customer satisfaction (Anggraini, Jodi, & Putra, 2020).…”
Section: Efek Mediasi Customer Satisfaction Pada Pengaruh E-service Q...unclassified
“…Keinginan konsumen untuk terus menggunakan layanan bergantung kepada keuntungan dan resiko dari layanan digital (Almasafri, 2022). Pengaruh tidak langsung dari e-service quality terhadap continuance intention to use didapat melalui efek mediasi customer experience serta customer satisfaction (Anggraini et al, 2020).…”
unclassified